ANALISIS PENERAPAN MEDIA INTERAKTIF BERBASIS LUMI EDUCATION DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPS - Gugun Darmawan; Gusnardi; Mujiono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Interactive learning media based on lumi education is an H5P-based tool used in learning by presenting content interactively, containing content in the form of a combination of various media into one unit in the form of images, videos and sounds. Learning motivation is a drive that arises from outside or inside students, which influences student behavior to achieve learning goals. This study aims to analyze the application of interactive media based on lumi education in increasing student learning motivation in social studies subjects. The study used a quantitative approach with a one-group pretest-posttest design. The research sample was 23 students of class VII C. Data collection was carried out through pretest and posttest questionnaires, then analyzed using paired sample t-test and N-Gain tests. The results showed that there was an increase in student learning motivation after the application of interactive media based on lumi education. This can be seen based on the paired sample T-test with a sig value of <0.001 < 0.05 so that it can be stated that H0 is rejected and H1 is accepted. And the N-Gain value of 0.63 or 63% is in the moderate category. Thus, lumi education-based interactive media is quite effective in increasing student learning motivation in social studies.